2014
DOI: 10.2341/13-062-l
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Adhesive Luting Agents to Caries-affected Dentin

Abstract: Caries-affected dentin could remain during conservative preparation for indirect restorations. However, the reduced bond strength of adhesive luting agents to this altered substrate might affect the longevity of restorations. SUMMARYIntroduction: The aim of this study was to evaluate the bond strength of adhesive luting agents to caries-affected dentin (CAD). Methods: Forty human molars were sectioned to create dental slices presenting exposed occlusal dentin. Half of the samples were submitted to eight caries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Other studies evaluating these two SARCs applied to sound dentin have had similar findings. 19,35,36 Differences in the composition of these two materials may explain these results. BisCem contains the highly hydrophilic monomer HEMA.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Other studies evaluating these two SARCs applied to sound dentin have had similar findings. 19,35,36 Differences in the composition of these two materials may explain these results. BisCem contains the highly hydrophilic monomer HEMA.…”
Section: Discussionmentioning
confidence: 74%
“…[14][15][16][17][18] By contrast, few studies have evaluated the bond strength of SARCs applied to CAD, and their results have been conflicting. 19,20 A recent study found no difference in SARC bond strength between natural CAD and sound dentin, 20 whereas another study using a pHcycling model to produce CAD found reduced bond strength to this substrate. 19 A difficulty of evaluating the bond strength of adhesive materials applied to CAD is standardizing the dentin substrate.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…12,13 The group, where restorations were cemented with regular cement, demonstrated better results when compared to self-adhesive resin cement groups, especially when the three-step etch-and-rinse adhesive system was applied, as previously shown. 14,15,16 Despite the low initial pH of the self-adhesive resin cement used, it presents low demineralization effect, and consequently, inadequate formation of the hybrid layer, 17,18 thus explaining the low bond strength values. On the basis of these results, the second hypothesis investigated, according to which the cementation strategy (type of resin cement) directly influences the bond strength of cemented composite resin restorations, can be accepted.…”
Section: Discussionmentioning
confidence: 99%